2015
DOI: 10.3109/15412555.2015.1057807
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease and its Non-Smoking Risk Factors in India

Abstract: The rising prevalence of the chronic obstructive pulmonary disease (COPD) is generally attributed to smoking, since the role of other risk factors among non-smokers are not well established especially in low and middle income countries like India. This is also reflected by the limited literature available on non-smoking related COPD risk factors like indoor and outdoor air pollution. The present review is an attempt to assess the influence of non-smoking risk factors on COPD and its measures in Indian subconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 106 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Smoking is by far the most common risk factor for development of COPD, but other factors such as outdoor, occupational, and indoor air pollution may also cause COPD in the absence of smoking. Factors such as genetics, infections, nutrition, and oxidative stress may also have a role in the development and/or progression of COPD (Walia, Vellakkal, & Gupta, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is by far the most common risk factor for development of COPD, but other factors such as outdoor, occupational, and indoor air pollution may also cause COPD in the absence of smoking. Factors such as genetics, infections, nutrition, and oxidative stress may also have a role in the development and/or progression of COPD (Walia, Vellakkal, & Gupta, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among these debilitating chronic conditions, COPD (chronic obstructive pulmonary disease) is currently the 3rd leading cause of death [3], although it is preventable by making early lifestyle changes such as completely avoiding tobacco smoking or exposure. It is well known that first and second hand cigarette smoke exposure is the leading cause of COPD initiation and progression [4], while other contributing risk factors are respiratory infections, air pollution, exposure to biomass-smoke or e-cig/nicotine-vapors, aging, certain genetic polymorphisms and obesity [49]. The continuous exposure of our airways to the plethora of noxious agents present in tobacco smoke and/or e-cig/nicotine vapors initiates inflammatory-oxidative stress that leads to the eventual irreversible damage of the lung parenchyma and alveolar walls [4, 10–12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is critical to identify risk factors in the management of COPD. Numerous studies of COPD prevalence have shown that male sex, older age, low education level, and tobacco use are associated with the development of COPD [7][8][9][10][11][12], but the risks identified in the studies performed in different regions varied. Therefore, a regional survey of COPD, as well as its risk factors, is still needed.…”
Section: Introductionmentioning
confidence: 99%